2023
DOI: 10.3389/fonc.2023.1086963
|View full text |Cite
|
Sign up to set email alerts
|

A huge verrucous carcinoma of the lower lip reconstructed by double Abbe flap: A case report and literature review

Abstract: Lip verrucous carcinoma is a rare low-grade neoplasm, with an unsightly appearance and locally aggressive nature. Treatment of verrucous carcinoma is as yet challenging, no well-defined guidelines for effective and safe management of this disease are available. A case of a patient with a huge verrucous carcinoma of the lower lip successfully treated by surgical excision and double Abbe flap reconstruction technique is presented, and striking features of lip locations of this tumor as well as their management a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…10 Chai et al described lower lip reconstruction in a patient with verrucous carcinoma using the Abbe's method by designing two symmetrical upper lip flaps to repair the lower lip defect and named this method as "Abbe double flap". 8 They found that a symmetrical approach in obtaining the two Abbe flaps was the best way to maintain the lower lip shape. They observed that the double flap technique is suitable for reconstructing large lip defects, avoiding trauma and other post-operative complications of other methods involving large incisions made on the face.…”
Section: Discussionmentioning
confidence: 99%
“…10 Chai et al described lower lip reconstruction in a patient with verrucous carcinoma using the Abbe's method by designing two symmetrical upper lip flaps to repair the lower lip defect and named this method as "Abbe double flap". 8 They found that a symmetrical approach in obtaining the two Abbe flaps was the best way to maintain the lower lip shape. They observed that the double flap technique is suitable for reconstructing large lip defects, avoiding trauma and other post-operative complications of other methods involving large incisions made on the face.…”
Section: Discussionmentioning
confidence: 99%